Multimorbidity profile in elderly market workers in Guanambi, Bahia (Research, Society and Development, 2020)
Objective: to analyze the factors associated with the multimorbidity of elderly market people. Method: This is an epidemiological, cross-sectional study based on data on sociodemographic aspects, lifestyle, health and work conditions reported by elderly workers in a municipal market. The inclusion criteria were elderly people aged 60 or over who carry out activities at the fair informally, that is, without registration in the work card and at a location specified by the market coordination. Results: 84 elderly people were found performing work activities in the municipal market, and of these workers, 40 reported having more than one morbidity (47.6%) framing the classification of multimorbidity. The highest prevalence of multimorbidity is among elderly women, aged 60 to 69 years, unmarried, education up to elementary school, black race / color, co-residents with other people, non-smokers, drink alcohol, do not perform physical activity, make use of medication, with a low or moderate capacity for work index, negative health perception, with low stress at work, working hours of up to 40 hours, sell fresh food and are satisfied with their work. Conclusion: the factors associated with multimorbidity found were medication use and work ability index.